2017
DOI: 10.1101/123265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysics and population size constrains speciation in an evolutionary model of developmental system drift

Abstract: Understanding the origin of species is as Darwin called it "that mystery of mysteries". Yet, how the processes of evolution give rise to non-interbreeding species is still not well understood. In an empirical search for a genetic basis, transcription factor DNA binding has been identified as an important factor in the development of reproductive isolation. Computational and theoretical models based on the biophysics of transcription factor DNA binding have provided a mechanistic basis of such incompatibilities… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…The epistatic relation between GRNs 2c.6 and 3.2 also exemplifies how hybrid incompatibilities could arise: certain crossings between individuals carrying these GRNs could lead to GRNs without a stripe phenotype. This is consistent with system drift being an important source of hybrid incompatibilities that cause reproductive isolation (Johnson and Porter, 2000, 2001; Khatri and Goldstein, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…The epistatic relation between GRNs 2c.6 and 3.2 also exemplifies how hybrid incompatibilities could arise: certain crossings between individuals carrying these GRNs could lead to GRNs without a stripe phenotype. This is consistent with system drift being an important source of hybrid incompatibilities that cause reproductive isolation (Johnson and Porter, 2000, 2001; Khatri and Goldstein, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…However, the pathway framework can be readily modified to include divergent selection and will almost certainly result in higher degrees of reproductive isolation. Fifth, recent work suggests that demographic complexity such as a varying population size can adds constraints on the process of speciation (Harvey et al, 2019;Khatri and Goldstein, 2019;Yamasaki et al, 2020;Momigliano et al, 2020). Future research may combine the pathway framework with additional demographic information to further investigate how ancestral genetic variation is sorted throughout the evolutionary trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…One question raised by founder effect speciation models is whether fluctuations of population size, such as those caused by founder events, may have a different effect on the accumulation of genetic incompatibilities when compared to constant (low) population size, as in our model. Khatri and Goldstein showed that genetic incompatibilities accumulate more quickly in smaller populations in several models of gene regulation 27,28,50 . Like our model, their models included strong incompatibilities that create holes in the fitness landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Khatri and Goldstein showed that genetic incompatibilities accumulate more quickly in smaller populations in several models of gene regulation 27, 28, 50 . Like our model, their models included strong incompatibilities that create holes in the fitness landscape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation